Some of my favorite "lesser known" problems - Rosenfeld, Moshe (Ars mathematica contemporanea, 2008)
Some problems become famous and attract attention while others collect dust on the shelf. Large conferences are a great breeding ground for popularizing both old and new problems. In this note we present some off the shelf problems.
Keywords: barvanje grafov; matematika; particije; teorija grafov